2016
DOI: 10.1039/c6ra14461f
|View full text |Cite
|
Sign up to set email alerts
|

An all-solid-state imprinted polymer-based potentiometric sensor for determination of bisphenol S

Abstract: An all-solid-state polymeric membrane potentiometric sensor for sensitive and selective determination of bisphenol S is developed for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…The amount of 2,4-DCP is estimated from the difference in potential between the baseline values and those at a fixed time (i.e., 100 s). At higher concentrations of DCP, we noticed stronger anionic response due to the more net movements of H + from the membrane to the aqueous phase [28]. The obtained results indicated that the electrodes revealed a potential response which is directly dependent on the concentration of neutral DCP.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The amount of 2,4-DCP is estimated from the difference in potential between the baseline values and those at a fixed time (i.e., 100 s). At higher concentrations of DCP, we noticed stronger anionic response due to the more net movements of H + from the membrane to the aqueous phase [28]. The obtained results indicated that the electrodes revealed a potential response which is directly dependent on the concentration of neutral DCP.…”
Section: Resultsmentioning
confidence: 98%
“…These unexpected anionic responses are due to the net movement of H + ions to the aqueous medium coming from the membrane. These H + were induced after the complexation of neutral phenols with the quaternary ammonium salt present in the sensing membrane [20,23,28].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, π–π interaction can occur between the aromatic moiety of the template with either the carboxylic group of MAA or the carbonyl group present in EGDMA. All of these types of interactions improve the binding affinity and specificity of the MIP [ 54 ]. A schematic representation of the imprinting process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…For a traditional ISE, the sensing membrane is usually conditioned with the primary ion and the electrodes are measured under classical equilibrium conditions for the Nernstian sensor response. In our previous work, it has been found that classical potentiometric sensors usually exhibit rather poor responses to ionic bisphenols, 13,28 while electrically neutral phenols and their derivatives could generate strong anionic potential responses on quaternary ammonium salt-doped polymeric membrane potentiometric sensors under near-neutral pH conditions. These unexpected anionic responses can be explained by the net movement of hydrogen ions from the membrane phase to the aqueous phase stimulated by neutral phenols.…”
Section: Potentiometric Detection Of Bpamentioning
confidence: 99%